Functionalization of Nanomaterials for Skin Cancer Theranostics - Chao Zhang; Xinlin Zhu; Shuming Hou; Weihua Pan; Wanqing Liao (Frontiers in Bioengineering and Biotechnology, 2022)
Skin cancer has drawn attention for the increasing incident rates and high morbidity worldwide. Timely diagnosis and efficient treatment are of paramount importance for prompt and effective therapy. Thus, the development of novel skin cancer diagnosis and treatment strategies is of great significance for both fundamental research and clinical practice. Recently, the emerging field of nanotechnology has profoundly impact on early diagnosis and better treatment planning of skin cancer. In this review, we will discuss the current encouraging advances in functional nanomaterials for skin cancer theranostics. Challenges in the field and safety concerns of nanomaterials will also be discussed.